A scoping review on clinicopathological characteristics, diagnosis, and management of intermammary pilonidal sinus disease - Sepalika Wijekoon; Hasthaka Dissanayake; Umayanga Dehigama; Jeewantha Senevirathna; Hasangi Gamage; N. P. M. Surage; G. K. P. M. Godakanda; Kanchana Wijesinghe (Women's Health, 2025)
Background: Intermammary pilonidal sinus disease (IMPSD) is a rare condition that primarily affects the young population. Due to the absence of standardized guidelines, IMPSD poses significant challenges during management. Objectives: This scoping review aims to map and characterize the existing literature on IMPSD to provide an overview of clinicopathological characteristics, risk factors, diagnosis, and management. Eligibility Criteria: Studies were included if they were original articles, case reports, or case series that met the inclusion criteria published in English during 2004 to 2024. Sources of Evidence: A search was conducted using MeSH keywords “Intermammary” AND “Pilonidal sinus” in PubMed, Google Scholar, and by citation searching up to date. Charting Methods: The PRISMA ScR guidelines were used as a charting method. Data extraction included demographic characteristics, clinical pathological characteristics, diagnostic methods, treatment approaches, and follow-up outcomes. Results: Ten articles met the inclusion criteria, including 33 patients with a mean age of 18.7 years. The majority of cases were reported from Turkey, Iraq, and India. Mean body mass index was 28.74 kg/m 2 . Significant other comorbidities included polycystic ovary syndrome in 24% of cases. Large pendulous breasts and wearing tight brassieres were noted as other risk factors. Clinical presentation commonly involved discharging sinuses and painful swellings, with a mean duration of 8 months. Complementary investigations were seldom performed as the diagnosis was mainly clinical. The main modes of treatment included resection with primary closure or resection with secondary healing. Conclusion: Low prevalence and management challenges highlight the need for further research to establish standardized guidelines and the importance of formulating an individualized plan for the management of IMPSD based on a comprehensive evaluation of clinicopathological characteristics and patient wishes.